2010
DOI: 10.1002/jcb.22633
|View full text |Cite
|
Sign up to set email alerts
|

AT‐101 (R‐(−)‐gossypol acetic acid) enhances the effectiveness of androgen deprivation therapy in the VCaP prostate cancer model

Abstract: Prostate cancer remains a leading cause of cancer death in American men. Androgen deprivation therapy (ADT) is the most common treatment for advanced prostate cancer patients; however, ADT fails in nearly all cases resulting in castration resistant or androgen-insensitive (AI) disease. In many cases, this progression results from dysregulation of the pro-survival Bcl-2 family proteins. Inhibition of pro-survival Bcl-2 family proteins, therefore, may be an effective strategy to delay the onset of AI disease. Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…13,84,86,87 In addition, studies indicate that gossypol activates p53 88 and therefore p53 might serve as a predictive biomarker for gossypol efficacy. Bladder cancer cell lines that are resistant to chemotherapeutic agents for metastatic bladder cancer in vitro, including gemcitabine and carboplatin, demonstrated significantly increased apoptosis under cotreatment with gossypol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,84,86,87 In addition, studies indicate that gossypol activates p53 88 and therefore p53 might serve as a predictive biomarker for gossypol efficacy. Bladder cancer cell lines that are resistant to chemotherapeutic agents for metastatic bladder cancer in vitro, including gemcitabine and carboplatin, demonstrated significantly increased apoptosis under cotreatment with gossypol.…”
Section: Resultsmentioning
confidence: 99%
“…In both non-CRPC and CRPC in vitro and in vivo models, gossypol has been shown to induce apoptosis as a single agent and to interact synergistically with standard therapies, such as docetaxel, radiation, and ADT. 13,84,86,87 In addition, studies indicate that gossypol activates p53 88 and therefore p53 might serve as a predictive biomarker for gossypol efficacy. Bladder cancer cell lines that are resistant to chemotherapeutic agents for metastatic bladder cancer in vitro, including gemcitabine and carboplatin, demonstrated significantly increased apoptosis under cotreatment with gossypol.…”
Section: Resultsmentioning
confidence: 99%
“…In initial studies, it has shown moderate single agent clinical activity in patients with relapsed and refractory CLL or NHL, but thrombocytopenia is a frequently encountered toxicity [40][41][42]. AT-101 is the isomer of gossypol, another orally available agent with varying affinities for various Bcl-2 family members [43][44][45]. It has shown modest single agent activity in castration-resistant prostate cancer, but significant gastrointestinal toxicity has been encountered [44].…”
Section: Other Bh3 Mimetic Small Molecule Inhibitors Of Bcl-2 Family mentioning
confidence: 99%
“…In the VCap human prostate cancer cell line, Bcl-2 expression was significantly upregulated in androgen independent cells in comparison to androgen-dependent cells, suggesting that abrogating Bcl-2 activity in combination with castration may delay onset of castrate resistant prostate cancer [11]. Further studies confirmed that in vitro , and in the VCaP prostate cancer xenograft, AT-101 was synergistic with androgen deprivation leading to decreased tumor volume, and delayed onset of androgen independence [11, 12]. Furthermore, androgen receptor activation by dihydrotestosterone attenuated AT-101-induced apoptosis, by upregulating Bcl-2 and Bcl-Xl, while inhibition of androgen receptor with bicalutamide restored AT-101-induced apoptosis, demonstrating that androgen deprivation and Bcl-2 inhibition act cooperatively to induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%